Can the Neutrinos from TXS 0506+056 Have a Coronal Origin? - Damiano F. G. Fiorillo; Federico Testagrossa; Maria Petropoulou; Walter Winter (The Astrophysical Journal)
The blazar TXS 0506+056 has been the first astrophysical source associated with high-energy astrophysical neutrinos, and it has emerged as the second-most-prominent hotspot in the neutrino sky over 10 yr of observations. Although neutrino production in blazars has traditionally been attributed to processes in the powerful relativistic jet, the observation of a significant neutrino flux from NGC 1068—presumably coming from the active galactic nucleus (AGN) corona—suggests that neutrinos can also be produced in the cores of AGN. This raises the question whether neutrino production in TXS 0506+056 is also associated with the core region. We study this scenario, focusing on the hypothesis that this blazar is a masquerading BL Lac object, a high-excitation quasar with hidden broad emission lines and a standard accretion disk. We show that magnetic reconnection is an acceleration process necessary to reach tens of PeV proton energies, and we use observationally motivated estimates of the X-ray luminosity of the coronal region to predict the emission of secondaries and compare them to the observed multiwavelength and neutrino spectra of the source. We find that the coronal neutrino emission from TXS 0506+056 is too low to describe the IceCube observed neutrinos from this AGN, which in turn suggests that the blazar jet remains the preferred location for neutrino production.